The Characteristics of Professional Administrators as Opinion by Teachers in Schools for the Deaf in Group 1 of Special Education Bureau - Seeno, Monruedee; Ruamchomrat, Pongsak; Pumklom, Mitparnee (Mahachula Academic Journal, 2023)
The research was to (1) study the characteristics of professional administrators as opinion by teachers’ schools for the deaf in group 1 of special education bureau, classified by teachers’ work experiences (2) Compare the characteristics of professional administrators according to the opinions of teachers of the Deaf School Group 1 of the Bureau of Special Education. Classified by teacher's work experience. The sample consisted of 130 teachers’ schools for the deaf in group 1 of special education bureau, obtained by simple random sampling. A constructed 5-level rating scale questionnaire with content validity at 1.00 and reliability at 0.96 was used as a tool to collect data. The statistics employed for data analysis were percentage, mean, standard deviation, one-way analysis of variance and a pair wise difference by means of Scheffe. The findings: (1) The characteristics of professional administrators as opinion by teachers’ schools for the deaf in group 1 of special education bureau. overall and each aspect at high level, ranking in order as follows : moral and ethical, academic leadership, leadership skills, knowledge and ability, new age skills and performance. (2) The results of comparing the characteristics of professional administrators as opinion by teachers’ schools for the deaf in group 1 of special education bureau, classified by teachers' work experiences. overall, there was a statistically significant difference at the 0.05 level, Teachers with more than 11 years of work experience had more opinions about the characteristics of professional administrators,Teachers with 5-10 years of work experience, performance were statistically significantly different at the 0.05 level, academic leadership and new age skills were statistically different at 0.01 level, Teachers with less than 5 years of work experience and more than 11 years of experience were more opinionated. Teachers with 5-10 years of work experience for performance Teachers with more than 11 years of work experience are more opinionated than teachers with 5-10 years of work experience.